POTENSI PEMANFAATAN SAMPAH MENJADI ENERGI KOTA BANJARMASIN BERDASARKAN KARAKTERISTIK KIMIA SAMPAH - Chaniago, Rian Yaitsar (Jurnal Daur Lingkungan, 2025)
Waste management operations in Banjarmasin City are still a regional challenge due to the closure of the Basirih landfill. This closure has an impact on waste transportation and disposal activities in Banjarmasin City. The implementation of a new waste paradigm that views waste as a resource can be a solution for waste management in Banjarmasin City. The method used is Tchobanoglous et al (1993). Data on waste generation and composition in Banjarmasin City were obtained from the national waste inventory website. There are 5 elements that can explain the amount of energy content in waste including carbon, hydrogen, oxygen, nitrogen, and sulfur. The analysis results show that the chemical formula of Banjarmasin City waste per day without sulfur content is C49H68O22N (without water) and C49H75O26N (with water). Meanwhile, the chemical formula with sulfur content is C804H1122O365N16S (without water) and C804H1245O427N16S (with water). The energy content using wet weight is 9,808 Btu/lb or 22,813 kJ/kg. While the energy content if the waste uses dry weight is 9,201 Btu/day or 21,402 kJ/kg. This indicates that Banjarmasin City can utilize waste into energy.